Disinformation and the Pandemic: The “Treacherous” Virus of Fake News - Pira, Francesco (Italian Sociological Review, 2023)
The pandemic represents a global emergency that has a profound impact on the lives of citizens. The contraction of spaces for personal freedom and the suspension of certain rights have altered the relationship between citizens and institutions, further modifying and weakening the dimension of the public sphere. This inherently unstable dimension is further weakened by a policy that exploits disintermediation for a construction of power based on the cancellation of the process of the acquisition of knowledge to leave space for the dynamics of polarisation and public opinion based on misinformation. The ongoing pandemic crisis represents a factor of profound destabilisation because it has exacerbated the phenomena already underway. Social distancing and physical immobility have definitively moved the construction of public discourse on the network, thus giving life to what is called platform society, where platforms produce the social structures in which we live (Van Dijck et al., 2018).